Hydrogen Embrittlement of Magnesium and Magnesium Alloys: A Review - Iannuzzi, Mariano; Kappes, M.; Carranza, R. (The Electrochemical Society, Inc, 2013)
Magnesium and magnesium alloys are susceptible to stress corrosion cracking in various environments, including distilled water. There is compelling evidence to conclude that SCC is assisted, at least in part, by hydrogen embrittlement. This paper reviews the thermodynamics of the Mg-H system and the kinetics of hydrogen transport. Aspects of magnesium corrosion relevant to hydrogen absorption are also discussed. Crack growth mechanisms based on delayed hydride cracking, hydrogen adsorption dislocation emission, hydrogen enhanced decohesion, and hydrogen enhanced localized plasticity have been proposed and evidence for each of them is reviewed herein.